2014
DOI: 10.1007/s40607-014-0009-9
|View full text |Cite
|
Sign up to set email alerts
|

The Sketch Engine

Abstract: The Sketch Engine is a leading corpus tool, widely used in lexicography. Now, at 10 years old, it is mature software. The Sketch Engine website offers many ready-to-use corpora, and tools for users to build, upload and install their own corpora. The paper describes the core functions (word sketches, concordancing, thesaurus). It outlines the different kinds of users, and the approach taken to working with many different languages. It then reviews the kinds of corpora available in the Sketch Engine, gives a bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
575
0
110

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,391 publications
(686 citation statements)
references
References 19 publications
1
575
0
110
Order By: Relevance
“…Research data was retrieved by means of the Sketch Engine (see Kilgarriff et al 2004), which enables collocations to be found using lexico-grammatical constructions. The program recognises collocations on the basis of the output of automatic morphological analysis (part of speech plus grammatical features) combined with statistical methods.…”
Section: Data and Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research data was retrieved by means of the Sketch Engine (see Kilgarriff et al 2004), which enables collocations to be found using lexico-grammatical constructions. The program recognises collocations on the basis of the output of automatic morphological analysis (part of speech plus grammatical features) combined with statistical methods.…”
Section: Data and Toolsmentioning
confidence: 99%
“…The corpus based study uses the Estonian Reference Corpus (203 million words altogether) where 75% of the texts are journalistic, so the results will mainly show how people are depicted in the media. Research data was retrieved by means of the Sketch Engine (see Kilgarriff et al 2004), which enables collocations to be found using lexico-grammatical constructions. Two lexico-grammatical constructions were analysed: the adjectival modifiers of nouns and verbs co-occurring with a noun functioning as a subject.…”
mentioning
confidence: 99%
“…WordSmith Tools 6.0 (Scott, 2008(Scott, , 2012 5. The Sketch Engine (Kilgarriff et al, 2004;Kilgarrif 2014) 6. IntelliText Corpus Queries (Wilson et al,.…”
Section: Tools Investigatedmentioning
confidence: 99%
“…The Sketch Engine (Kilgarriff et al, 2004(Kilgarriff et al, , 2014) is a commercial webbased tool for corpus analysis developed by Lexical Computing Ltd. In addition to the corpora searching tool, the users are provided with corpora in many languages including Arabic.…”
Section: Sketch Enginementioning
confidence: 99%
See 1 more Smart Citation